2021
DOI: 10.3390/app112210567
|View full text |Cite
|
Sign up to set email alerts
|

Buzz Tweet Classification Based on Text and Image Features of Tweets Using Multi-Task Learning

Abstract: This study investigates social media trends and proposes a buzz tweet classification method to explore the factors causing the buzz phenomenon on Twitter. It is difficult to identify the causes of the buzz phenomenon based solely on texts posted on Twitter. It is expected that by limiting the tweets to those with attached images and using the characteristics of the images and the relationships between the text and images, a more detailed analysis than that of with text-only tweets can be conducted. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The text features of the tweets were extracted by using the pre-trained BERT model, and the image features were obtained from pre-trained models such as VGG16. The results of the experiments showed that the correct response rate for predicting buzz classes with the proposed method using both text and image features was higher than when using the text or image features alone [36].…”
Section: Retweet Prediction Based On Heterogeneous Data Sourcesmentioning
confidence: 94%
See 1 more Smart Citation
“…The text features of the tweets were extracted by using the pre-trained BERT model, and the image features were obtained from pre-trained models such as VGG16. The results of the experiments showed that the correct response rate for predicting buzz classes with the proposed method using both text and image features was higher than when using the text or image features alone [36].…”
Section: Retweet Prediction Based On Heterogeneous Data Sourcesmentioning
confidence: 94%
“…In addition to retweet prediction, heterogeneous feature sources have also been successfully used to predict buzz tweets. Amitani et al [36], in their study on the classification of "buzz" tweets, examine the trends on social media and propose a classification method to study the factors that cause the buzz phenomenon on Twitter. This phenomenon can be understood as an explosion of popularity within a short period of time.…”
Section: Retweet Prediction Based On Heterogeneous Data Sourcesmentioning
confidence: 99%
“…The text features of the tweets were extracted using the pre-trained BERT model, and the image features were obtained from pre-trained models such as VGG16. The results of the experiments showed that the correct response rate for predicting buzz classes with the proposed method using both text and image features was higher than using the features alone [28].…”
Section: Retweet Prediction Based On Heterogeneous Data Sourcesmentioning
confidence: 96%
“…In addition to retweets, heterogeneous feature sources have also been successfully used to predict buzz tweets. Amitani et al in [28], in their study on the classification of "buzz" tweets, examine the trends in social media and propose a classification method to study the factors that cause the buzz phenomenon on Twitter. This phenomenon can be understood as an explosion of popularity within a short period of time.…”
Section: Retweet Prediction Based On Heterogeneous Data Sourcesmentioning
confidence: 99%
“…Amitani et al [4] constructed a model to discriminate buzz tweets from text with images posted on Twitter using multi-task learning. Their method is similar to the present study in that it uses only the information at the time of tweet posting.…”
Section: Introductionmentioning
confidence: 99%